A portfolio approach to the optimal mix of funded and unfunded pensions. Issue 16 (2nd April 2020) - Bouhakkou, Léa; Coën, Alain; Folus, Didier
ABSTRACT: In this paper, we address the optimal funding of pensions by means of portfolio choice approach. Considering the unfunded (Paygo) pension system as a 'quasi-asset' with hedging and diversification properties, we derive the optimal portfolio mix of funded and Paygo systems within a mean variance and Bell linear exponential models. Our analysis involves both analytical computations and empirical estimations of optimal values using real long-term data for equity, bonds and the Paygo asset for several OECD countries and several time periods covering the time span 1897–2016. We find that in most cases a mix of both systems is desirable with a larger magnitude of Paygo system in the case of the Bell framework as we capture attitudes towards asymmetry and tail risks that are typical to equity markets.